Kajian Pengembangan Wisata Religi Berbasis Sosial Masyarakat di Pura Uluwatu - Awaloedin, Dipateruna; Pradini, Gagih; Kusumaningrusm, Anisa Putri; Ardani, Putri Aulia; Sanjaya, Surya (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine (1) the history of the establishment of Uluwatu Temple in Pecatu Village; (2) the development of Uluwatu Temple, as a tourism destination in Bali; and (3) the contribution of Uluwatu Temple to local tourism. This study uses a qualitative approach, namely: (1) research methods; (2) several determinations of research locations; (3) techniques for determining local residents' informants; (3) data collection techniques (interviews, document studies); (4) data analysis techniques. The results of this study indicate that there are two sources regarding Uluwatu Temple, namely written sources and oral sources. The development of Uluwatu Temple as a tourist attraction in Bali, Contributions of the existence of Uluwatu Temple for historical education include: (a) several studies of worship at Uluwatu temple, (b) Fostering students' love for historical / cultural heritage which is Balinese ancestral heritage, (c) Fostering historical awareness and cultural insight in students to participate in maintaining and preserving ancient / historical relics that are around us, (d) A visit to Uluwatu Temple can help to gain a deeper understanding of learning materials on campus related to local tourism materials